2014 World Figure Skating Championships in Reus: feedback from participants and economic legacy - Murillo, C.; Carles, M.; Llop, M.; Moya, X.; Planas, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The last days of September and beginning of October 2014 was held in the city of Reus Artistic Skating World Championships. This event welcomes the different types of skating and brought together about 1,200 athletes and 20 thousand spectators. The degree of satisfaction among athletes reached the score of 8.5 out of 10, while among the audience was 8.1 note. The loyalty expressed favorably since 95% of respondents would recommend attending a show of similar characteristics, while 90% of athletes are also evident in this sense. The estimated direct spending that has reversed in the territory is estimated at 2.1 million euros. The investment multiplier was 3.22, while the multiplier on the consumption reached the figure of 2.29 for the expenditure of the organization and spending 2.71 assistants. In overall, it is estimated for the whole economy of Catalonia a positive effect by 5.5 million euros. The most benefited sectors from these effects are tourism (22.8%), trade (14.8%), business services (14.2%) and transport and communications (10%).